2009
DOI: 10.3141/2126-01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bond Strength of Tack Coat Materials in Field

Abstract: The results presented in this paper are part of NCHRP Project 9-40 on the Optimization of Tack Coat for Hot-Mix Asphalt Placement. This paper presents the development of a new test device, the Louisiana Tack Coat Quality Tester (LTCQT), for evaluating the quality of the bond strength of tack coat in the field. LTCQT is a modification of the ATacker device. A test matrix was developed to evaluate the reliability and the repeatability of the LTCQT in the field. Three emulsified tack coats (CRS-1, SS-1h, and Trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 2 publications
0
44
0
Order By: Relevance
“…Findings from NCHRP Project 09-40 using three surface texture conditions (open graded friction course [OGFC], sand mixture, and stone mastic asphalt [SMA]) found a pronounced effect of texture, with a spread in ISS of approximately 20 pounds per square inch (psi) between surface texture extremes and at relatively similar residual application rates to those used in this study ( 1 ). The field prepared specimens tested during the NCHRP study exhibited substantially lower ISS values for the same application rate and the same mixture materials ( 1 ). Further, results of NCHRP Project 9-40A demonstrated that the ISS values measured with test method AASHTO TP 114 correlated well with short-term cracking performance at six field sites with different climatic conditions and traffic levels ( 5 ).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Findings from NCHRP Project 09-40 using three surface texture conditions (open graded friction course [OGFC], sand mixture, and stone mastic asphalt [SMA]) found a pronounced effect of texture, with a spread in ISS of approximately 20 pounds per square inch (psi) between surface texture extremes and at relatively similar residual application rates to those used in this study ( 1 ). The field prepared specimens tested during the NCHRP study exhibited substantially lower ISS values for the same application rate and the same mixture materials ( 1 ). Further, results of NCHRP Project 9-40A demonstrated that the ISS values measured with test method AASHTO TP 114 correlated well with short-term cracking performance at six field sites with different climatic conditions and traffic levels ( 5 ).…”
mentioning
confidence: 59%
“…This was required because the test fixture cannot hold the two parts of the sample without confinement. It is worth noting that the same confinement pressures have been used in other ISS Studies ( 1 , 10 ). The shearing load in all cases was applied at a constant rate of 2.54 mm/min on the sample until failure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Illustration of the aluminum slice between upper and lower layer of asphalt mixture. (2) Direct Shear Apparatus Direct shear tests were carried out to measure the interface shear strength between upper and lower layers of asphalt mixture under the conventional and the double-decked paving method[25,26]. As shown inFigure 4, the test apparatus (Yaxing Equipment of Civil Engineering Limited, Xi'an, China) consists of a shear box, a loading rod, a load cell and a motor.…”
mentioning
confidence: 99%
“…The performance of thin lifts of HMA placed on top of existing pavements depends on the quality of the bond between new and existing surfaces. The shear strength developed by tack-coated interfaces has been shown to be temperature dependent ( 16 ). The shear and tensile strength of the bond provided by tack coats is one of the factors potentially leading to debonding issues and associated cracking.…”
mentioning
confidence: 99%